Strategi Pembelajaran Guru PAI bagi Tunawicara - Pamungkas, Eqviesta Runtun; Husna, Difa Ul; Agustin, Eviana; Yuliana, Vita (TSAQOFAH, 2022)
Learning strategies in teaching and learning activities for children with special needs with speech impairments are of particular concern. This study aims to find out the most appropriate strategy in teacher or educator learning for children with special needs for speech impairment. The research method used is regular review by taking several articles as references. The search results for related journals were obtained from several journals which were analyzed using data techniques related to the theme. The researcher also made observations at the Sentolo Republic of Indonesia Teachers Association Special School to complete the data. The results of this study are finding the right formula in dealing with children with special needs with speech impairments in teaching and learning activities. From the results of this study, educators can easily use this strategy in teaching and learning activities. A child with special needs for speech impairment should be properly sent to school. This is important because a mute person also has the right to get a proper education. In addition, the ability to communicate with people with hearing impairments is not easy because they have to learn sign language.